META ANALISIS: EFEKTIVITAS PENGGUNAAN MEDIA KOMIK DALAM PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Alfira Novita Candrayani; Yohana Dian Ambarwati; Handoko Wibisono (STKIP Subang, 2024)
This meta-analysis aims to investigate the successful use of comics media in improving learning achievement of Pancasila Education at the elementary school level. By collecting and qualitative evaluating various previous studies, this research highlights the benefits of using comics in increasing students' interest, motivation and understanding of the learning material. The results of the analysis show that comic media can serve as an effective learning tool in teaching Pancasila Education, with its ability to stimulate students' creativity and reinforce local values contained in the curriculum. The implications of these findings suggest that the utilization of comic media can have a positive impact in basic learning, particularly in the context of Pancasila values education.